Analysis of the Effect of Asset Allocation on Portfolio Performance with Diversification as an Intervening Variable - Dipa Teruna Awaludin; Hasanudin; Faysal Deni Rahman (GoAcademica Research & Publishing, 2021)
This study aims to analyze the effect of asset allocation on portfolio performance with diversification as an intervening variable in the Pension Fund, a non-bank financial institution that manages the pension program and is registered and supervised by the Financial Services Authority (OJK) in the 2016-2019 period. A total of 34 Pension Funds were sampled so that the total sample was 136 in the 2016-2019 period. Data analysis using Structural Equation Modeling (SEM). The results showed that Selection Ability and Fund Size had a significant effect on Diversification, while Timing Ability had a significant effect on Portfolio Performance. Intervening test using Sobel Test shows that Diversification has not been able to mediate Asset Allocation on Portfolio Performance.